2003
DOI: 10.1016/s0109-5641(03)00007-1
|View full text |Cite
|
Sign up to set email alerts
|

Surface analysis of dental amalgams by X-ray photoelectron spectroscopy and X-ray diffraction

Abstract: Objectives : It is important to characterize the surface of dental amalgam in order to understand the process of mercury release from amalgam restorations in the oral. The mercury evaporation occurs not only from the newly made restoration but also from the set material. Methods :The surfaces of four different types of amalgams, which had been well set, were analyzed with X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) and the relationship between surface compositions and mercury release was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
3
5
1
Order By: Relevance
“…The total amount of mercury estimated for ANA 2000 in the conducted study was significantly smaller than the data obtained during investigations of this material carried out by Uo et al [11]. The experiment described by Hanawa [8] showed that the mercury concentration within the surface film of a fresh specimen was similar to that in the bulk.…”
Section: Discussioncontrasting
confidence: 64%
See 4 more Smart Citations
“…The total amount of mercury estimated for ANA 2000 in the conducted study was significantly smaller than the data obtained during investigations of this material carried out by Uo et al [11]. The experiment described by Hanawa [8] showed that the mercury concentration within the surface film of a fresh specimen was similar to that in the bulk.…”
Section: Discussioncontrasting
confidence: 64%
“…Furthermore, silver and copper enabled the second stage of the amalgamation reaction, eliminating the transient ␥ 2 phase [11]. Uo et al [11] revealed that the oxygen content on a fresh ANA 2000 amalgam surface was 33 at%, compared to significantly less, 6.38 at%, in our study. Furthermore, the atomic oxygen concentration obtained by McDermott et al [7] for fresh Sybralloy HCSS amalgam (45.4 at%) was similar to the results of the XPS analysis of Safargam (48.78 at%) and Megalloy (52.21 at%).…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations